Prekarno delo skozi prizmo delovnega prava - Kresal Šoltes, Katarina (Delavci in delodajalci, 2019)
Through the prism of labour law, precarious work is a logical negation of the decent work concept. Since the beginning of the implementation of the nonstandard forms of work, labour law studies have warned against their negative effects on workers, labour markets and society as a whole, due to their potential decent work deficits, which in turn presents a risk of precariousness. Academic discourse on potential methods of addressing this phenomenon through labour regulation at the EU and national level continues to flourish. Present discussion was triggered by the recently published book "Precarious work: The Challenge for Labour Law in Europe".
Keywords: decent work; delovna razmerja; delovno pravo; employment relationship; European social model; labour law; precarious work; prekarno delo; socialna varnost